Clonal variation in the intensity of powdery mildew (Oidium heveae steinm) disease of Hevea - John A; Joseph A; Meenakumari T; Saraswathyamma C K; Varghese Y A (Indian Journal of Natural Rubber Research, 2000)
Twenty genotypes representing gene pools of diverse origin were screened in the nursery with the objective of identifying soures of resistance against Oidium heveae Steinm. causing powdery mildew incidence. An attempt was also made to understand the pattern of response of the genotypes in different years. Clonal variation for the intensity of powdery mildew was highly significant. Among the 20 genotypes studied, eight genotypes viz., RRIC 52, AC/S/12 42/186, PR 261, RO/CM/10 44/7, RRIM 703, AC/S/12 42/59, PB 86 and IAN 45-873 possessed high degree of tolerance combined with stability in their response to disease intensity.
Keywords: Disease intensity; Hevea; POwdery mildew; Response pattern; Stability